Evaluating the Impact of Basic Design Fundamentals Education on the Creative Process of Fashion Design Students in Surabaya, Indonesia - Prianka, Dian (Abdul Media Literasi, 2023)
This academic paper explores the influence of Basic Design Fundamentals (BDF) education on the creative process of fashion design students in Surabaya, Indonesia. BDF education, rooted in the principles of design, serves as a foundational element in various design disciplines, including fashion. The study employs a mixed-method research approach, combining quantitative Likert scale assessments and qualitative interviews with ten students from the University of Surabaya's fashion design program. The research reveals that BDF education significantly enhances the creative abilities of fashion design students in Surabaya. The majority of participants strongly agree that BDF education positively impacted their creative process, resulting in more visually appealing and well-structured designs. Moreover, BDF education empowers students to strike a balance between creative intuition and systematic thinking, fostering innovative design solutions. However, some participants suggest the need for a more direct application of BDF principles to fashion design projects to bridge the gap between theory and practice effectively. Overall, this study underscores the vital role of BDF education in nurturing creativity and problem-solving skills among fashion design students in Surabaya. The findings offer valuable insights for curriculum development, emphasizing the potential benefits of integrating theoretical design principles with practical applications, thereby enhancing the quality and competitiveness of fashion design graduates. Future research may explore the broader applicability of these findings across diverse cultural and educational contexts.